A SEMIÓTICA GREIMASIANA NAS CANÇÕES INFANTIS DO ÁLBUM CRIANCEIRAS - MARIA LUCIA AMARAL MUNIZ (2021)
This work has as theoretical foundation the greimasian semiotics. We propose to perform the semiotic analysis of the text of two children's songs by the composer Márcio de Camillo, whose theme is the poetry of Manoel de Barros. The methodology of analysis consists in the use of the generative course of sense as a methodological reading resource to understand the sensible sense of children's songs, as well as the sound and timbristic aspects. The analysis through the methodological process that includes the generative path of the sense is based on (Cf. BARROS, 2005), (DISCINI, 2002), (BERTRAND, 2003), (GREIMAS, 1966) and others. Where we consider the three levels of analysis: fundamental, narrative and discursive. The corpus analyzed are two juvenile songs by the composer Márcio de Camillo cutout of CD Crianceiras. We seek to identify: a) the actants of the utterance: the "me/you"; b) the space of the utterance; c) the contrast between positive and negative values; d) the verb tenses that are part of the utterance; e) the issue of euphoria and dysphoria, among others. Besides performing the textual analysis of the songs, we also analyze the thematic and figurative images, with the purpose of observing the sound image through the descriptive conduct for the visualization of how the relation between the lyrics and the song occurs (TATIT, 2003). Thus, our results focus on the perspective of contributing to the expansion of the studies on the greimasian semiotics 6 applied to the object of analysis of the children's song, notably concerning the two compositions by Márcio de Camillo. Keywords: Greimasian Semiotics; Sensitive perception; Children's song; Marcio de Camillo.